Rhythm techniques in the poetry of Hasab Al-Sheikh Jaafar - Mayyada AbduLAmeer ISmael ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study seeks to explore the techniques of rhythm in modern Arabic poetry through the poetic works of Haseb al-Sheikh Jaafar, one of the most prominent figures of modernism in Arabic literature. His poetic experience is distinguished by the employment of innovative techniques, some of which pertain to the overall rhythm of the poem, while others relate to its stylistic structure. Accordingly, this research aims to identify the most significant rhythmic techniques utilized by the poet and to examine their role in enhancing the rhythmic dimension of the poem. The research adopts an analytical descriptive method.